Finding an Alternative to Formalin for Sterilization of Extracted Teeth for Teaching Purposes. Issue 1 (1st January 2013) - Hope, Christopher K.; Griffiths, David A.; Prior, Daniel M.
Abstract : Formalin is a known carcinogen, so there is a need to establish whether a safer alternative is available for the sterilization of human teeth destined for use in clinical training. Any disinfectant that is not capable of sterilizing 100 percent of the samples tested should be considered a failure. In this study, biofilms of oral bacteria were grown on previously autoclaved extracted human teeth. These biofilm‐laden teeth were then screened against a range of disinfectants for an exposure time of seven days in a laboratory refrigerator. Culture methods were employed to validate the sterility of the tooth samples. Five percent Virkon and Gigasept PA proved effective against the laboratory model of disinfection and were carried forward to challenge freshly extracted human teeth. Gigasept PA was the only disinfectant that sterilized 100 percent of the tooth samples. Gigasept PA should be considered a safer and effective alternative to formalin for the sterilization of extracted teeth destined for teaching purposes.